Durability analysis of bio‑cemented slope soil under the exposure of acid rain. - Gowthaman, S.; Nakashima, K.; Kawasaki, S. (Springer, 2021)
Purpose: Instability of slope surface is a critical concern in Geotechnical and Environmental Engineering. MICP (Microbial-Induced Carbonate Precipitation), an innovative bio-cementation technique, has attracted the attention for slope surface protection. In this work, MICP was investigated to evaluate its durability under the exposure of acid rain and to advance the understanding on long-term performance of slope soil preserved by MICP. Methods: MICP treatment was applied to a fine-grained slope soil using indigenous bacteria. Specimens treated to different cementation levels (% CaCO3) were exposed to acid rain (of varying pH) through two sorts of mechanisms: (i) infiltration and (ii) immersion. The evaluations were based on corrosion of CaCO3, mass loss, needle penetration tests, and scanning electron microscopy. Results: The decrease in pH increased the corrosion of CaCO3, resulting in considerable loss in aggregate and unconfined compressive strength. However, increased cementation level showed high durability of specimens. The soils treated to 12.5% CaCO3 showed 19.9% soil loss, whereas it was reduced to 5.4% when cemented to 22.5% CaCO3. The results also revealed that the contact time of acid rain significantly governed the rate of corrosion, i.e., specimens subjected to lower infiltration rate (20 mm/h) showed higher loss of mass compared to that of higher rate (100 mm/h). Conclusion: The long-term performance of MICP treatment is determined by (i) cementation level, (ii) pH, and (iii) infiltration rate of acid rain. High cementation level promotes the longevity of the treatment. Therefore, MICP to higher cementation level is recommended for long-term preservation of slope surface.
Keywords: : Microbial-induced carbonate precipitation (MICP); Slope surface; Preservation; Durability; Long-term performance; Cementation level